2013
DOI: 10.1111/jrh.12028
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Depressive Symptoms in Older Rural Couples: The Impact of Work, Stress and Health

Abstract: Stress management may be particularly important in older farm couples, since perceived duress of 1 member of the dyad impacts both. Work factors and health conditions also affect depressive symptoms in older rural couples, but these may be less easily modified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 53 publications
1
30
3
Order By: Relevance
“…Rather, the TWH approach advocates for a holistic understanding of the factors that contribute to worker wellbeing. Scientific evidence now supports what many workers have long suspected: that risk factors in the workplace can contribute to health problems previously considered unrelated to work (i.e., work-related risk factors for obesity (Champagne et al, 2012;Luckhaupt, Cohen, Li, & Calvert, 2014), sleep disorders (Caruso, 2014) Calvert, 2014) and depression (Arcury, Grzywacz, Chen, Mora, & Quandt, 2014;Rayens & Reed, 2014;Wulsin, Alterman, Bushnell, Li, & Shen, 2014). To reiterate, the TWH approach integrates workplace interventions that protect safety and health with activities that advance the overall well-being of workers.…”
Section: • • Twh Is Not a Collection Of Health Promotion Effortsmentioning
confidence: 89%
“…Rather, the TWH approach advocates for a holistic understanding of the factors that contribute to worker wellbeing. Scientific evidence now supports what many workers have long suspected: that risk factors in the workplace can contribute to health problems previously considered unrelated to work (i.e., work-related risk factors for obesity (Champagne et al, 2012;Luckhaupt, Cohen, Li, & Calvert, 2014), sleep disorders (Caruso, 2014) Calvert, 2014) and depression (Arcury, Grzywacz, Chen, Mora, & Quandt, 2014;Rayens & Reed, 2014;Wulsin, Alterman, Bushnell, Li, & Shen, 2014). To reiterate, the TWH approach integrates workplace interventions that protect safety and health with activities that advance the overall well-being of workers.…”
Section: • • Twh Is Not a Collection Of Health Promotion Effortsmentioning
confidence: 89%
“…Farmers have reported workload and time constraints, uncertainty in job and financial markets, governmental involvement, physical isolation, family conflicts, and succession of the farm as a few of the stressors that impact their mental health (Truchot & Andela, ). Additional factors that may contribute to depressive symptoms include work patterns, satisfaction with farm work, and overall health (Rayens & Reed, ).…”
Section: Discussionmentioning
confidence: 99%
“…44 Our study found that farmers' perceived threatened independence contributed to suicidality. 44 Stress management has been posited as important for older farm couples, 45 while integrating mental health care into primary care has been suggested as an effective strategy for identifying and treating older people with physical conditions and suicidality. 44 Similarly observed by Creighton and colleagues, 9 maladaptive coping responses among farmers were identified, with self-medicating indicated.…”
Section: Discussionmentioning
confidence: 99%